Urgensi kewenangan pengawasan OJK terhadap kegiatan penghimpunan dana oleh lembaga non keuangan - Salsha Zuhriyah; Tunggul Anshari Setia Negara; Endang Sri Kawuryan (University of Merdeka Malang, 2021)
This paper aims to analyze the urgency of the supervisory authority of the Financial Services Authority (OJK) on fundraising activities by non-financial institutions. For the purpose of discussion, this type of normative legal research uses a statutory approach, an analytical approach, and a case approach. Primary and secondary legal materials were analyzed using grammatical and systematic analysis techniques. Based on the results of the discussion, it was concluded that the Financial Services Authority's supervisory authority over the activities of collecting funds by non-financial institutions was that the Financial Services Authority had no authority. Based on the provisions of Articles 4, 5, 6, and Article 34 of the BI Law and their explanations regarding the regulation of OJK's supervisory functions, objectives, and authorities, it can be concluded that OJK's supervisory authority is limited to only covering financial service sector institutions, both banks, and non-banks. Meanwhile, First Travel is categorized as a non-financial institution in the form of a travel agency for Hajj and Umrah, although First Travel carries out fundraising activities. It is also strengthened that First Travel is not an official entity under the authority of the OJK in terms of licensing, regulation and supervision. First Travel status has received permission from the Ministry of Religion of the Republic of Indonesia but raises funds that are not in accordance with the license held. So, in the case of First Travel, it should have been sufficiently handled by the Ministry of Religion of the Republic of Indonesia, because that ministry was the one that issued permits and carried out supervision.How to cite item: Zuhriyah, S., Negara, T., Kawuryan, E. (2021). Urgensi kewenangan pengawasan OJK terhadap kegiatan penghimpunan dana oleh lembaga non keuangan. Jurnal Cakrawala Hukum, 12(3), 344-354. doi:https://doi.org/10.26905/idjch.v12i3.4965.